Performance Evaluation Against Cost and Time Using Earned Value Analysis (EVA) and Mean Absolute Percentage Error (MAPE) - Desma Samosir; Retna Kristiana; Sediyanto Sediyanto (Universitas Tribhuwana Tunggadewi Malang, 2026)
Development in the construction sector is rapidly advancing with technological progress. This research focuses on the Damaged Fence Repair project in Karawang, which has a total work length of 780 meters. This project is a response to fence damage that limits the area of PT. Pindo Deli is located along the river flow and in residential areas. However, the project's implementation has been delayed and is estimated to be completed on April 22, 2025. The delay occurred after the progress reached 507 meters due to various factors. To address this issue, the Earned Value Method (EVM) is used to assess cost and time performance, and the Mean Absolute Percentage Error (MAPE) is used to measure the accuracy between the plan and the actual results. This analysis is expected to contribute to service providers considering similar future projects. The research results indicate that the implementation is not on schedule, with a total cost of Rp. 2,199,059,894.34. The cost performance index (CPI) shows a value of less than 1, indicating waste, while the schedule performance index (SPI) is less than 1, indicating delays. There was a time deviation from the 18-week plan to 22 weeks, and a cost deviation of Rp. 509,880,654.62. The MAPE for time was 22.59% and for cost 17.05%, indicating good accuracy. This research provides a significant methodological contribution by integrating EVA performance metrics with MAPE accuracy analysis, offering a more comprehensive evaluation framework that not only identifies deviations but also validates the reliability of planning estimates, which serves as a strategic model for optimizing project control in specialized industrial infrastructure repairs.